2007
DOI: 10.1002/asi.20584
|View full text |Cite
|
Sign up to set email alerts
|

Google Scholar citations and Google Web/URL citations: A multi‐discipline exploratory analysis

Abstract: In this paper we introduce a new data gathering method "Web/URL Citation" and use it and Google Scholar as a basis to compare traditional and Web-based citation patterns across multiple disciplines. For this, we built a sample of 1,650 articles from 108 Open Access (OA) journals published in 2001 in four science and four social science disciplines. We recorded the number of citations to the sample articles using several methods based upon the ISI Web of Science, Google Scholar and the Google search engine (Web… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
152
0
3

Year Published

2007
2007
2013
2013

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 201 publications
(163 citation statements)
references
References 41 publications
8
152
0
3
Order By: Relevance
“…The results correlate significantly with Web of Science citations (Kousha & Thelwall, 2007) and incorporate a range of source documents, including, but not limited to, publishers' digital libraries. This is effectively a hybrid web/journal database source, but seems to be heavily focused on academic sources and does not permit automatic searching in a way that would be necessary for automatic IF calculations for journals, unless provided by Google.…”
Section: Web Citationsmentioning
confidence: 64%
See 2 more Smart Citations
“…The results correlate significantly with Web of Science citations (Kousha & Thelwall, 2007) and incorporate a range of source documents, including, but not limited to, publishers' digital libraries. This is effectively a hybrid web/journal database source, but seems to be heavily focused on academic sources and does not permit automatic searching in a way that would be necessary for automatic IF calculations for journals, unless provided by Google.…”
Section: Web Citationsmentioning
confidence: 64%
“…Web citations for articles in individual journals, as described above, have been shown to correlate significantly with traditional Web of Science citations for many disciplines (Kousha & Thelwall, 2007;Vaughan & Shaw, 2003. A web citation -hyperlink hybrid measure, URL citations, has also been shown to correlate significantly with citations (Kousha & Thelwall, 2007).…”
Section: Web Citationsmentioning
confidence: 92%
See 1 more Smart Citation
“…Journal coverage in these databases is also dramatically lower in the Social Sciences than in the Sciences. For instance, Kousha & Thelwall (2007) found that around 77% (49 of 64) of their selected journals in science disciplines, but only 13% (6 of 44) of social science journals were indexed in the Web of Science.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, other authors have evaluated the impact of academic journal articles through various online measurements (Kousha & Thelwall, 2007;Vaughan & Shaw, 2003), the impact (loosely speaking) of authors online (Cronin, Snyder, Rosenbaum, Martinson, & Callahan, 1998) and the spread of an issue online (Thelwall, Vann, & Fairclough, 2006). Nevertheless, no previous research has set out and evaluated a method for estimating the impact of nonacademic reports (e.g., white papers, online magazines or newsletters, promotional leaflets) using online methods.…”
Section: Introductionmentioning
confidence: 99%